School performance: An IDEB analysis of the seven municipalities in the ABC region - Garcia, Paulo Sérgio; Prearo, Leandro Campi; Romero, Maria do Carmo; Secco, Anderson; Bassi, Marcos Sidnei (Revista Eletrônica de Educação, 2016)
<!–[if gte mso 9]> <![endif]–> The quality of basic education in Brazil has been monitored, especially by the Basic Education Development Index (Índice de Desenvolvimento da Educação Básica – IDEB), created in 2007. This index combines students’ achievement in the System of Assessment for Basic Education (Sistema de Avaliação da Educação Básica- SAEB) for states and, the Brazilian Exam (Prova Brasil) for municipalities, with the school flow (taking into account dropout numbers). This study analyzes the IDEB of the seven municipalities in the ABC region, performing multiple comparisons using mixed methodology. It was analyzed the IDEB of each city, regarding the schools’ level of education (Elementary School I and II). It was considered in the analysis, the schools development, with regard to achieving the goals established by the different administrative spheres and by INEP, as well as, the proportion of students who reached the appropriate level in the competences of reading, reading comprehension and the competence of problem solving. At the same time, all the information that contextualized the quantified data was analyzed with school Principals. The results showed gradual and continuous evolution in the index of Elementary School I in municipal and state spheres, and minimal growth or stagnation in Elementary School II. An even harder reality is presented in mathematics learning. At the data contextualization, the absence of positive continuity from the results of Elementary School I, to Elementary School II, was attributed to the characteristics of each segment, such as the number of teachers, the type of treatment given to the student, the methods used, the references shared and accepted, the school organization, and the school management. This data may assist the schools in the qualitative improvement of education in the cities of the region. Keywords: School performance. IDEB in the ABC region. Elementary school. Quality of education. <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>